Penentuan Biaya Preservasi Berdasarkan Analisa Nilai Pemicu IRI PCI dan Lendutan Perkerasan pada Jalan Nasional di Sulawesi Utara - Eucharis Daud Mongisidi; Joice Waani; Lucia Lefrandt (Jurnal Teknik Sipil Terapan, 2023)
Samratulangi Street, R.W. Monginsidi Street, Bethesda Street and Pierre Tendean Street are national roads in North Sulawesi. At first glance, these four roads are in good, moderate and slightly damaged condition. Based on their status, these road sections were examined to see the relationship between IRI, PCI and Deflection and calculate the cost of preservation measures. Functional conditions on four national roads from 3.81 to 8.53 for IRI and 69 to 100 for PCI, while Structural Conditions range from 91.4 µm to 542.5 µm for maximum deflection, 120.55 µm to 4602.99 µm for the surface layer, 14.7 µm to 447.4 µm for the base layer, 20.1 µm to 259.9 µm for subbase layer, and 22.4 µm µm to 66.7 µm for subgrade layer. While the elastic modulus of the surface layer ranges from 536.06 Mpa to 270302.05 Mpa, the elastic modulus of the top layer is 40.53 MPa to 3111.77 Mpa, the elastic modulus of the subgrade layer is 80.54 MPa to 2428.48 MPa, and the elastic modulus of the subgrade layer is 86.89 MPa to 868.84 MPa. Project version preservation cost Rp.33,951,452,569. The functional condition analysis version is Rp.37,164,723,427 difference (Rp.-3,213,270,858), and the structural condition analysis version is Rp.76,977,602,855 difference (Rp.-43,026,150,286). The results are expected to provide information to the road management authority regarding the relationship between the level of damage and the amount of costs. Kata kunci - preservation cost, fwd, iri, pci